Intestinal Microbiota-Associated Metabolites: Crucial Factors in the Effectiveness of Herbal Medicines and Diet Therapies - Wang, Yiliang; Qin, Shurong; Jia, Jiaoyan; Huang, Lianzhou; Li, Feng; Jin, Fujun; Ren, Zhe; Wang, Yifei (Frontiers in Physiology, 2019)
Although the efficacy of herbal medicines (HMs) and traditional Chinese medicines (TCMs) in human diseases has long been recognized, their development has been hindered in part by a lack of a comprehensive understanding of their mechanisms of action. Indeed, most of the compounds extracted from HMs can be metabolized into specific molecules by host microbiota and affect pharmacokinetics and toxicity. Moreover, HMs modulate the constitution of host intestinal microbiota to maintain a healthy gut ecology. Dietary interventions also show great efficacy in treating some refractory diseases, and the commensal microbiota potentially has significant implications for the high inter-individual differences observed in such responses. Herein, we mainly discuss the contribution of the intestinal microbiota to high inter-individual differences in response to HMs and TCMs, and especially the already known metabolites of the HMs produced by the intestinal microbiota. The contribution of commensal microbiota to the inter-individual differences in response to dietary therapy is also briefly discussed. This review highlights the significance of intestinal microbiota-associated metabolites to the efficiency of HMs and dietary interventions. Our review may help further identify the mechanisms leading to the inter-individual differences in the effectiveness of HM and dietary intervention from the perspective of their interactions with the intestinal microbiota.